Neuro-cognitive specificities in prosocial disobedience: A comparative fMRI study of civilian and military populations - Leslie Tricoche; Antonin Rovai; Salvatore Lo Bue; Emilie A. Caspar (PLoS ONE, 2025)
The literature highlighted that compliance with or resistance to authority orders to inflict pain involves cognitive processes like empathy, guilt, mentalization, cognitive conflict, and sense of agency. However, previous studies have focused on civilians, for whom such decisions are less significant than for military personnel, where obedience or resistance is integral to duty. This functional Magnetic Resonance Imaging (fMRI) study examined 53 military personnel, compared to 56 civilians, tasked with deciding whether or not to deliver shocks to a victim following orders received by an experimenter. Results revealed that military participants disobeyed orders less frequently, adopting higher homogeneous profiles: fewer ultra-prosocial and no antisocial behavior. High disobedience in military participants was driven by rational (moral, educational) and emotional factors (guilt, sadness, heightened victim sensitivity). Shared neuro-cognitive processes were observed between the two populations, but the level of engagement of these processes differed. While civilians predominantly recruited left temporo-parietal junction (TPJ) and dorso-medial prefrontal cortex (dmPFC) during decision-making, military agents relied more heavily on regions such as the right TPJ and anterior insula to achieve disobedience. Military participants also exhibited a reduced sense of agency in prosocial disobedience compared to civilians. In post-decision when witnessing the victim’s pain, military participants preferentially activated right-hemisphere regions, while civilians engaged more left and medial regions. These differences suggest distinct mentalization forms, with civilians favoring cognitive empathy and military personnel relying more on affective empathy. These findings could have implications for ethics training in military and institutional contexts, and offer insights into how obedience and resistance are cognitively and emotionally constructed across different social roles and institutional environments.